Pengaruh Ekstrak Etanol Kulit Jeruk Nipis (Citrus Aurantifolia (Christm.) Swingle) Terhadap Penyembuhan Ulkus Traumatik pada Rattus Norvegicus Strain Wistar - Wardani, Resti Puspita, drg. Mahmud Kholifa, MDSc, drg. Sartari Entin Yuletnawati, MDSc (2015)
Traumatic ulcer is an inflammation on oral mucous caused by traumatic injury such as thermal, chemical, radiation, mechanic and electric injury. One of the alternative therapy was using ethanolic extract of lime carp. Ethanolic extract of lime carp was a product from lime carp maceration which had anti-inflammatory agents and supporting wound healing process. The research aims were to know the effect and the effective concentrations of ethanolic extract of lime carp on traumatic ulcer healing of Rattus norvegicus strain Wistar. The true experimental laboratory with posttest only control group design was confirmed in this research. Twenty four Wistar rats were exposed to a drop of perhidrol on the lower lip's mucous to induced ulceration. Two drops of 6,25%; 12,5%; 25% and 50% ethanolic extract of lime carp, aquades as negative control and Aloclair as positive control were applied on the same area twice a day for each groups. Final diameters of ulcer were measured using sliding caliper on the fifth day. The results indicated that ethanolic extract of lime carp had enhancing traumatic ulcer healing with p = 0.001. The effective concentrations were on 25-50% consentrations of lime carp ethanol extract. In conclusion, ethanolic extract of lime carp (Citrus aurantifolia (Christm.) Swingle) had effect on traumatic ulcer healing of Rattus norvegicus strain Wistar.